Resident and teacher perceptions of the preceptor field note: A qualitative analysis - Markovski, Milena; Jeyabalan, Vyshnave; Stephens, Robert; Kiehn, Lana; Lockwood, Jonathan; Saeed, Danyal; Bordman, Risa (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2024)
Implication StatementAssessment of clinical teachers is a requirement by family medicine residency programs in Canada. This facilitates feedback to teachers and ensures the curriculum is delivered in an efficient and safe way. To protect resident confidentiality, preceptors often receive their teaching evaluations months to years later. Teachers have requested shorter feedback loops, greater numbers, and more frequent assessments to improve their skills.The preceptor field note (PFN) is a tool that allows learners to evaluate teachers during a single encounter providing more frequent and immediate feedback. This study documents teachers’ and residents’ initial impressions of the first iteration of the PFN.